The Teachers’ Mining Tour in Ontario: A Professional Development Program for Educators - Hymers, Lesley; Steer, Bill; Williams, Janice (Geoscience Canada, 2015)
The Teachers’ Mining Tour is a professional development program for educators hosted at the Canadian Ecology Centre (CEC) located near Mattawa, Ontario. Each year in late summer for three years (2010–2012) approximately thirty Ontario teachers participated in a five day program that included presentations by mineral industry professionals, site visits to mines and mine manufacturing operations, and educational resource workshops. In 2013, to meet demand, the Tour program was expanded to include two tours, annually. The goal of the Tour is to provide teachers with the information and resources that they need to become more proficient Earth Science teachers and to educate their students about the mining industry and, through this increased knowledge and experience, to encourage their students to pursue post-secondary education and careers in Earth Sciences and mining-related disciplines. Additional objectives are to create and cultivate a network of teachers using mining as a theme in their classrooms, and to promote informed opinions amongst participants with regard to the economic, social and environmental aspects of mining. The Tour content focuses on modern mining techniques and technology, environmental responsibility, workplace safety, and mining careers. Tours consistently receive favourable reviews from teachers, industry participants and representatives from sponsor organizations. In addition to the feedback sought through evaluation forms at the conclusion of each Tour program, additional feedback is sought from participants in the following spring of each academic year. A formal survey is circulated, providing teachers with the opportunity to report back about how their Tour experience is influencing their teaching. Respondents report that they are satisfied with the information and resources that they received during the Tour, that the program is directly applicable to the subjects that they are teaching, and that their perceptions about mining changed because of their experience.